Ankle Complex Neuromuscular Coordination Variation in People Living with HIV (International Journal of Physiotherapy, 2021)
Background: People living with HIV (PLHIV) can exhibit impaired postural control because of infection or secondary medication effects, even with no history of falls. In PLHIV, balance deficits are associated with neuromuscular activation variations, muscle weakness, and complications with the vestibular and proprioceptive systems. We intend to determine neuromuscular activation coordination patterns of the tibialis anterior (TA) and gastrocnemius (GA) during eight different balance activities in physically active PLHIV.Methods: 55 participants were recruited to participate in this non-randomized control trial, 24 of whom had been diagnosed with HIV. We collected the neuromuscular profile from both groups to assess TA and GA muscle activity during static balance tasks with and without cognitive dual tasking.Results: Neuromuscular coordination patterns were dissimilar (p-value ≤ 0.05) in the HIV group in GA onset during eyes open on foam (EO FOAM), GA and TA duration and decay activity during eyes closed on foam (EC FOAM), and duration during eyes-closed head up and down (EC HUD). No considerable differences (p-value > 0.05) were observed with the addition of a cognitive task.Conclusion: During the disease's controlled stages, HIV or its medications cause a miscommunication between the ankle complex musculature and the vestibular input related to postural control. These neuromuscular modifications are more noticeable in single tasks requiring higher recruitment of the vestibular input to sustain balance, such as an unstable surface with no visual information. Directions for subsequent investigation include gathering participants with various physical activity levels, medications, CD4 counts, lengths of time since diagnosis, and examining balance during more advanced tasks, such as dynamic balance activities and motor dual-tasking.Clinical Relevance: Identify balance disturbances in PLHIV to reduce or prevent the risk of falls or injury. Specific deficits identified in PLHIV can be used to tailor interventions and address the balance systems at fault.